2007
DOI: 10.1021/ma062225l
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α,ω-Dimercapto Poly(N-isopropylacrylamides) by RAFT Polymerization with a Hydrophilic Difunctional Chain Transfer Agent

Abstract: A new hydrophilic difunctional reversible addition-fragmentation chain transfer (RAFT) agent, diethylene glycol di(2-(1-isobutyl)sulfanylthiocarbonylsulfanyl-2-methylpropionate) (DEGDIM) was synthesized and shown to be effective in imparting living characteristics to the radical polymerization of N-isopropylacrylamide (NIPAM), providing a route to telechelic poly(N-isopropylacrylamides) (PNIPAM) of predictable molecular weights and narrow molecular weight distributions. The thiocarbonylthio end groups were tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 38 publications
1
84
0
Order By: Relevance
“…C Compounds not used as RAFT agents directly but served as precursors to other RAFT agents. [370] Poly(dimethylsiloxane) macro-RAFT agent DMAM [370] DMAM-b-HEA [370] 188 [371,372] [371][372][373] 189 [374] C [374] 190 [286] NIPAM [286] St [286] (NIPAM-b-St) [286] St-b-NIPAM [286] (Continued) [286] St [286] (NIPAM-b-St) [286] St-b-NIPAM [286] 192 [375] …”
Section: S S S O Hn Possmentioning
confidence: 99%
See 2 more Smart Citations
“…C Compounds not used as RAFT agents directly but served as precursors to other RAFT agents. [370] Poly(dimethylsiloxane) macro-RAFT agent DMAM [370] DMAM-b-HEA [370] 188 [371,372] [371][372][373] 189 [374] C [374] 190 [286] NIPAM [286] St [286] (NIPAM-b-St) [286] St-b-NIPAM [286] (Continued) [286] St [286] (NIPAM-b-St) [286] St-b-NIPAM [286] 192 [375] …”
Section: S S S O Hn Possmentioning
confidence: 99%
“…It was reported that aminolysis of PNIPAM trithiocarbonate proceeds quantitatively to the thiol when conducted in the presence of a [370] MMA Ph (28) AIBN [173] MMA Ph (28) 393 [173] MMA C 10 H 7 (42) AIBN B [194] 416 Ph (25) ACVA C [164,474] DMAPMAM Ph (25) AIBN [168] NIPAM C 2 H 5 S (185) 394 [368] NIPAM C 2 H 5 S (189) 394 [374] NIPAM C 12 H 25 S (139) AIBN [324] NIPAM S(PDMAM-b-PNIPAM) (398) AIBN [475] DMAM S(PDMAM) (398) AIBN [475] NAM/NAS C 12 H 25 S (115) AIBN [299] St Ph (24) AIBN [133] St C 4 H 9 S (160) AIBN D [473] St Ph (50) 395 [476] St S(PSt) (398) AIBN [475] VAc small amount of a phosphine reducing agent (TCEP). [371,372] Two groups have compared aminolysis with borohydride reduction for PSt dithiobenzoate. [117,205] One study [205] compared (a) sodium borohydride in aqueous THF, (b) sodium borohydride in toluene with phase transfer catalysis, (c) lithium triethylborohydride in THF, and (d) propylamine in THF.…”
Section: Aminolysis/hydrolysis/ionic Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…au) or V. Bulmus (E-mail: vbulmus@unsw.edu.au) been the removal of the RAFT end-group by reduction or aminolysis 5,6,48,52-59 yielding functional polymers 27,60,61 and polymers with thiol end-groups that can be further modified. 54,56,[62][63][64] This aminolysis approach has a potential serious drawback, as the resultant thiol is susceptible to further oxidation to disulfide leading to bimodal polymer populations composed of thiol and disulfide functional polymers. [53][54][55][56]59,60,65,66 To overcome this problem, our group and others have reported an approach employing aminolysis of the RAFT-end groups in the presence of thiol-reactive compounds such as pyridyldisulfide-bearing 40,67,68 or ene-bearing compounds, 54,56,61,64 leading to simultaneous protection/functionalization of the created thiols.…”
Section: Introductionmentioning
confidence: 99%
“…[7] These methods include radical processes, [8,9] thermolysis, [10][11][12] hydride reduction, [13][14][15] hydrolysis, [16] aminolysis [5,[17][18][19][20][21] and so forth, among which the aminolysis route has been more competitively exercised. Indeed, aminolysis of RAFT polymers is very efficient under mild conditions, and more importantly aminolysis produces highly reactive polymer thiols that have been appreciated in the synthesis of telechelic functional polymers, [5,15,17,20,[22][23][24][25][26] star polymers, [27] block copolymers, [21,23,28] polymer networks/ gels, [29,30] polymer bioconjugates, [25] as well as in the decoration of metal surfaces [14,31,32] and in the selective functionalisation of core-shell nanogels. [22,33] Typically, primary amines are used in the aminolysis of RAFT polymers and under such basic conditions thiols are highly susceptible to oxidation by oxygen in air through a base-catalysed radical process.…”
Section: Introductionmentioning
confidence: 99%